Reforma al artículo 133 del código de planificación y finanzas públicas con el objetivo de garantizar la ejecución y sostenibilidad de los proyectos de inversión de los gobiernos autónomos descentralizados - Villacis Rivas, Piedad Eugenia (2015)
The plan to pose as legal research to methodological development Preliminary final report of my thesis requirement is based on the treatment of a relevant subject in the area of strategic and participatory planning in Ecuador, directed to identify limitations and shortcomings type structural and policy in the field of public finances. More specifically the subject area has its legal basis in the field of regulation of the Code of planning and public finance, legal body that was published in the second supplement to Official Gazette No. 306 of 22 October 2010; The wording of art. 1 aforementioned legal body can infer the object and purpose of this legal instrument that accurately determines the following: "Art.- 1. This Code aims to organize, regulate and link the National Decentralized Participatory Planning System with the National System of Public Finance, and regulate its operation at different levels of the public sector under the regime development, good living arrangements, guarantees and constitutional rights. The provisions of this Code governing the exercise of the powers of planning and carrying out public policy at all levels of government, the National Development Plan, development plans and land use of the autonomous governments, budget planning four-year Public Sector, the General State Budget, other budgets of public entities; and all public funds and other instruments applicable to the Planning and Finance. " Firstly giving the National Secretariat of Planning and Development discretion to determine which investment projects submitted by GADs can have the quality of priority in order to authorize a loan; then allow for injection of resources; besides empowered the governing body of public finances in the country, the power to determine how conditions should be restored and the loan granted in this case to GAD, which implies involvement of regional decentralized principle of these governments that it Constitution has called them autonomous.